2020
DOI: 10.1101/2020.08.24.265637
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The putative phosphate transporter PitB (PP1373) is involved in tellurite uptake in Pseudomonas putida KT2440

Abstract: Tellurium oxyanions are chemical species with great toxicity; their presence in the environment has increased because of mining industries and photovoltaic and electronic waste. Recovery strategies based on microorganisms for this metalloid are of interest, but further studies of the transport systems and enzymes responsible for implementing tellurium transformations are required because many mechanisms remain unknown. Here, we investigated the involvement in tellurite uptake of the putative phosphate transpor… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(12 citation statements)
references
References 37 publications
(59 reference statements)
1
11
0
Order By: Relevance
“…Furthermore, a previous report by Sanchez-Romero et al (1998) demonstrated that a recombinant strain of P. putida KT2440 transformed with tellurite resistance (Tel R ) plasmids or transposons can grow in potassium tellurite concentrations up to 315 μM, proving that tel resistance genes can be used as selection markers for manipulating Pseudomonas strains. In addition, it was recently reported (Montenegro et al, 2021) that in this bacterium the unspecific putative phosphate transporter (PitB) is involved in tellurite uptake, however, it is suspected that P. putida can use other transporters for this process (Montenegro et al, 2021). The same study confirmed the reduction of tellurite and the formation of black nano-sized and rod-shaped tellurium particles after culturing the bacterium for 24 h with 100 μM of tellurite although the mechanism of the reduction is unknown (Montenegro et al, 2021).…”
Section: àmentioning
confidence: 71%
See 4 more Smart Citations
“…Furthermore, a previous report by Sanchez-Romero et al (1998) demonstrated that a recombinant strain of P. putida KT2440 transformed with tellurite resistance (Tel R ) plasmids or transposons can grow in potassium tellurite concentrations up to 315 μM, proving that tel resistance genes can be used as selection markers for manipulating Pseudomonas strains. In addition, it was recently reported (Montenegro et al, 2021) that in this bacterium the unspecific putative phosphate transporter (PitB) is involved in tellurite uptake, however, it is suspected that P. putida can use other transporters for this process (Montenegro et al, 2021). The same study confirmed the reduction of tellurite and the formation of black nano-sized and rod-shaped tellurium particles after culturing the bacterium for 24 h with 100 μM of tellurite although the mechanism of the reduction is unknown (Montenegro et al, 2021).…”
Section: àmentioning
confidence: 71%
“…obtain elemental metals (or even nanoparticles) by the reduction of oxyanions (Avendaño et al, 2016;P aez-Espino et al, 2020;Montenegro et al, 2021). Thus, we propose Pseudomonas as an adequate biotechnological chassis for the recovery of metals and metalloids, which are naturally scarce but have been recently in high demand due to their use in electronic devices.…”
Section: The Redox Potential Of Members Of the Pseudomonas Genusmentioning
confidence: 99%
See 3 more Smart Citations